Dynamic Modeling and Simulation of Rough Cylindrical Micro/Nanoparticle Manipulation with Atomic Force Microscopy. (7th October 2014) - Korayem, Moharam H.; Badkoobeh Hezaveh, Hedieh; Taheri, Moein
Abstract In this paper, the process of pushing rough cylindrical micro/nanoparticles on a surface with an atomic force microscope (AFM) probe is investigated. For this purpose, the mechanics of contact involving adhesion are studied first. Then, a method is presented for estimating the real area of contact between a rough cylindrical particle (whose surface roughness is described by the Rumpf and Rabinovich models) and a smooth surface. A dynamic model is then obtained for the pushing of rough cylindrical particles on a surface with an AFM probe. Afterwards, the process is simulated for different particle sizes and various roughness dimensions. Finally, by reducing the length of the cylindrical particle, the simulation condition is brought closer to the manipulation condition of a smooth spherical particle on a rough substrate, and the simulation results of the two cases are compared. Based on the simulation results, the critical force and time of manipulation diminish for rough particles relative to smooth ones. Reduction in the aspect ratio at a constant cross-section radius and the radius of asperities (height of asperities based on the Rabinovich model) results in an increase in critical force and time of manipulation.